Into the realm of organizational folly: A poem, a review, and a typology of organizational stupidity. Issue 2 (April 2023) - Azevedo, Guilherme
This 'Provocation essay' is aimed at triggering reflection and fostering renewed research into organizational stupidity and its intersections with management learning. It opens with a critical poem evoking diverse aspects of our daily encounters with the idiocy, nonsense, and absurdity that pervades organizations. It continues with a more comprehensive review of the still diffuse research literature to reveal a typology of three approaches to studying organizational stupidity (systemic-mechanistic, critical-sociological and cultural-functionalist). It closes with a discussion of how stupidity detracts from reflexivity but can also play useful roles in organizations, which ultimately invites more management learning research on the topic.